2007
DOI: 10.1007/s10350-007-9031-4
|View full text |Cite
|
Sign up to set email alerts
|

Timeline of Recurrence After Primary and Secondary Pilonidal Sinus Surgery

Abstract: Long-term recurrence rate was 22 percent and thus higher than previously reported. This may be attributed to the long follow-up interval. Recurrences up to 20 years after surgery were seen. Our data provide evidence that follow-up after first to the third pilonidal sinus surgery should complete or exceed five years, because the majority of recurrences occur during this postoperative interval. Nevertheless, even a five-year follow-up will still miss 25 percent of recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 25 publications
5
102
1
6
Order By: Relevance
“…Its prevalence is 1-4 per 25000 population, with a 40% five-year recurrence rate (1)(2)(3). Approximately 70% of PSD patients are between 20-30 years of age (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its prevalence is 1-4 per 25000 population, with a 40% five-year recurrence rate (1)(2)(3). Approximately 70% of PSD patients are between 20-30 years of age (4).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors include obesity, smoking, poor hygiene, sedentary life style, African race, family history, and high amount of hair on the body. The recurrence rates for PSD after lay open and primary closure techniques are 17% and 30%, respectively (1). Primary closure techniques are divided into two main categories.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 205 military patients followed for a median of 14.8 years, Doll et al found a bimodal peak of disease recurrence following excision and primary closure with early recurrences occurring in the first four years. 26 They suggested that a follow-up duration of at least five years is required to detect 75% of recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the minimal surgical procedure recurrence, rates increased over the span of a year (7). Many publications have shown that recurrence occurred in the first 5 years (19)(20)(21). Soll et al demonstrated that recurrence rates for PS treated with the minimal surgical procedure increased annually, and they gave the recurrence rates as 6.5%, 13.2%, and 16.2% for the first year, the first 5 years, and the first 10 years, respectively (7).…”
Section: Discussionmentioning
confidence: 99%